Analisis Keandalan Sistem Keselamatan Bangunan Terhadap Bahaya Kebakaran (Studi Kasus: Gedung Rumah Sakit Ibu Dan Anak Eria Bunda Kota Pekanbaru) - Pratama, Rangga; Trikomara, Rian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The research was done by applying a tool checks reliability of building against fire on Eria Bunda Mother and Children Hospital City of Pekanbaru. This examination aims to determine the level of reliability in the form of building Value Reliability System Safety Building (NKSKB) against fire which is the total percentage of the sum of the percentage of building safety system components (KSKB) the completeness tread, means of rescue, passive protection system and active protection system . The results in the form of value system reliability against fire safety of building (NKSKB) in building Eria Bunda Mother and Children Hospital with 17,03% tread completeness assessment, system safety means 16,35%, 17,68% passive protection system and active protection system 6,18%. The level of reliability of fire protection systems in building Eria Bunda Mother and Children Hospital as a whole is "Less" with a percentage of 57,24%.Keywords: completeness tread, means of rescue, passive protection system, active protection system.